(untitled) (Research, Society and Development, 2020)
The objective of this study was to evaluate the influence of drying temperature of Bixa orellana L leaves. the biological properties of the essential oils (EOs) obtained. The plant material a was collected and submitted to a convectiva greenhouse of air at temperatures 35-55 °C. The EOs were obtained by hydrodistillation. The antimicrobial assay was performed using the Disk Diffusion Method against Staphylococcus aureus and Escherichia coli. For the biotoxicity assay, the lethality of the EOs in front of Artemia salina was evaluated. Significant differences were observed in the properties of OE’s. The temperature of 45 °C allowed to obtain the most efficient bactericidal action against the microorganisms tested and the toxicity was also verified for the EO obtained at this temperature. This study concludes through the analyzed activities that the drying temperature influences the properties of EOs and the temperature of 45° is stated as the most indicated for B. orellana due to the better performance of the properties both in the antimicrobial assay and toxicity.